Herbal Extract as An Antibacterial Against Gram Positive Bacteria Causing Dermatitis Complex - Suartha, I Nyoman; Suarjana, I GustiKetut; Sudimartini, Luh Made; Merdana, I Made; Swantara, I Made Dira (Journal of Veterinary and Animal Sciences, 2017)
Study in order to evaluate the antibacterial effect of herbal extract from leaves of three different species of plant namely neem(Azadirachtaindica A. Juss), gotu-kola (Centellaasiatica), andsoursop (Annona muricata L) against bacteria causing dermatitis complex in dogs have been undertaken. The antibacterial activities of the herbal extract were evaluated using the agar diffusion test with extract at three different concentrations 5%, 10%, and 25%, respectively.Staphylococcus aureus was isolated from the dermatitis complex cases in dogs. The results showed various antibacterial activities of all the herbal extract at all concentration as indicated by the diameter of inhibition haloes produced around the orifice. The average inhibition haloes for each herbal extract concentration was 2.19± 0.53 mm; 4.32± 0.84 mm; 5.86± 0.79 mm, respectively. It can be concluded that herbal extract from the three plants is a potential antimicrobial against agents causing dermatitis complex.